Stratospheric ozone depletion during the 1995–1996 Arctic winter: 3-D simulations on the potential role of different PSC types - J. Hendricks; F. Baier; G. Günther; B. C. Krüger; A. Ebel (Annales Geophysicae, 2001)
The sensitivity of modelled ozone depletion in the winter Arctic stratosphere to different assumptions of prevalent PSC types and PSC formation mechanisms is investigated. Three-dimensional simulations of the winter 1995/96 are performed with the COlogne Model of the Middle Atmosphere (COMMA) by applying different PSC microphysical schemes. Model runs are carried out considering either liquid or solid PSC particles or a combined microphysical scheme. These simulations are then compared to a model run which only takes into account binary sulfate aerosols. The results obtained with the three-dimensional model agree with trajectory-box simulations performed in previous studies. The simulations suggest that conditions appropriate for type Ia PSC existence ( T < T NAT ) occur over longer periods and cover larger areas when compared to conditions of potential type Ib PSC existence. Significant differences in chlorine activation and ozone depletion occur between the simulations including only either liquid or solid PSC particles. The largest differences, occurring over large spatial scales and during prolonged time periods, are modelled first, when the stratospheric temperatures stay below T NAT , but above the threshold of effective liquid particle growth and second, in the case of the stratospheric temperatures remaining below this threshold, but not falling below the ice frost point. It can be generally concluded from the present study that differences in PSC microphysical schemes can cause significant fluctuations in ozone depletion modelled for the winter Arctic stratosphere. Key words. Atmospheric composition and structure (aerosols and particles; cloud physics and chemistry; middle atmosphere composition and chemistry)